Educational System Building in a Changing Educational Sector: Environment, Organization, and the Technical Core. Issue 6 (September 2019) - Spillane, James P.; Seelig, Jennifer L.; Blaushild, Naomi L.; Cohen, David K.; Peurach, Donald J.
The institutional environment of U.S. school systems has changed considerably over a quarter century as standards and test-based accountability became central ideas in policy texts and discourses about improving education. We explore how U.S. school systems are managing in this changed environment by focusing on system leaders' sense-making about their environments as they attempt to build educational systems to improve instruction, the core technology of schooling. We identify the policy texts and discourses system leaders notice and their framings, interpretations, and uses of these cues as they build educational infrastructures to support more coherent instructional visions. We argue that school systems' educational infrastructure building efforts were intended at coupling their systems' formal organization with particular environmental cues in an effort to influence classroom instruction. In turn, we argue that these educational infrastructure building efforts can simultaneously be motivated by, and in pursuit of, institutional ritual and technical rationality.